Calibrated ages of Mawnbwll Du Mawr (MBM) peat core from Wales - Donna Carless (PANGAEA, 2021)
Calibrated ages of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.